Assessing the use of social media for employee engagement in the Singapore military - Tan, Kok Yew (2017)
This study assesses the potential of social media in the engagement of employees, particularly in the military, through literature review and interviews with current and former employees from the Singapore military. The possible role and application social media could have on military employee engagement are derived through the study of the characteristics of employment in a military and non-military organization, and the transferability of employee engagement strategies across both organizational settings. The transferability of the essences of literature on employee engagement are specifically possible by studying the employees’ informational and emotional needs through the lenses of Social Identity Theory (Taifel & Turner, 1979) and Affect Control Theory (Heise, 1979), which add on to Bray, Marsden and Peterson’s (1991) argument that the employees are similar in their values and needs as the military employees were drawn from the civilian population while the organizational setting might differ. As Generation Y (Gen Y) dominates the working population worldwide and blurs the possible divide between the characteristics between military and civilian employees with their informational and emotional needs (Trunk, 2007; Yeaton, 2008; Solnet, Kralj & Kandampully, 2012), this study postulates the applicability of its findings from the Armed Forces in Singapore beyond its confines.